The Study on Gelatine Addition to Acidity, pH, Water Holding Capacity and Syneresis of Yogurt - Manik Eirry Sawitri; Abdul Manab; Theresia Wahyu Lebdo Palupi (Faculty of Animal Science Universitas Brawijaya, 2008)
The objective of this study to find out the effect of gelatine addition as a stabilizer on acidity, pH, water holding capacity, and syneresis of yogurt. The material of these research were yogurt made from skim milk with 14% of total solid, yogurt starter which combination of Lactobacillus bulgaricus and Streptococcus thermophillus (1:1), and gelatine as a stabilizer. The method was experiment using Randomized Block Design, which the factor was the gelatine percentage (w/v) of 0 % (G0), 0.2% (G2), 0.4 % (G4), and 0.6 % (G6). The observed variables were syneresis, water holding capacity, acidity, and pH. Data was subjected to analysis of variance followed by Duncanâ€™s Multiple Range Test. The result of analysis variance showed that the addition of gelatine did not gave Â a significant effect (P>0.05) on acidity, significant effect (P<0.05) on pH and highly significant effect (P<0.01) on syneresis and water holding capacity of yogurt. It was concluded that the addition of gelatine as a stabilizer influences pH, water holding capacity and syneresis but gave no influence acidity of yogurt. The addition of 0,6% gelatine as a stabilizer could produce yogurt with low syneresis, high water holding capacity, and the normal pH. Keywords: Yogurt, gelatine, acidity, pH, water holding capacity, syneresis